An evaluation of the comprehensive rural development programme (CRDP) highlighting environmental governance in the Eastern Cape - Mkhutshulwa, Ndabakazi Thabile (Stellenbosch : Stellenbosch University, 2017)
Thesis (MPhil)--Stellenbosch University, 2017.